2019
DOI: 10.1055/s-0039-1693443
|View full text |Cite
|
Sign up to set email alerts
|

Once Upon a Rhinoplasty: The History of the “Queen” of Facial Plastic Surgery

Abstract: The history of rhinoplasty is absolutely fascinating. It is replete with mysterious practices, intrigue, and imaginative thoughts. If necessity is the mother of invention, then sex, crimes, and punishment lay a legitimate claim to being the mother of rhinoplasty. The history of rhinoplasty is a global saga spanning the millennia. Practitioners of the art and science have included those demonstrating the most admirable traits espoused in the Hippocratic Oath, as well as those to whom the word “charlatan” might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 173 publications
0
4
0
Order By: Relevance
“…The preservation or improvement of proper nasal The Merits of the External Rhinoplasty Gantous, Ziai function has become a mandatory consideration in well-performed rhinoplasty. [41][42][43][44][45][46] We believe that, following the concepts of open structure rhinoplasty, this open approach helps us to more easily improve or restore a better airway in our patients. Similarly, authors have suggested that avoiding incisions in the inter-cartilaginous region may prevent disruption of the caudal end of the nasal valve region, which is critical to the overall functional and aesthetic result.…”
Section: Preservation Of Nasal Functionmentioning
confidence: 95%
“…The preservation or improvement of proper nasal The Merits of the External Rhinoplasty Gantous, Ziai function has become a mandatory consideration in well-performed rhinoplasty. [41][42][43][44][45][46] We believe that, following the concepts of open structure rhinoplasty, this open approach helps us to more easily improve or restore a better airway in our patients. Similarly, authors have suggested that avoiding incisions in the inter-cartilaginous region may prevent disruption of the caudal end of the nasal valve region, which is critical to the overall functional and aesthetic result.…”
Section: Preservation Of Nasal Functionmentioning
confidence: 95%
“…In addition, 1997 saw the formation of the International Federation of Facial Plastic Surgery Societies, which in 2012 established its board examination to be held each year in Washington and London. 59 In 2021, there is an overabundance of courses and meetings available for surgeons in training. Some are run by selfproclaimed experts, some by interest groups, some by universities, some by national societies, and some by international societies.…”
Section: Postresidency Surgical Educationmentioning
confidence: 99%
“…While conflicting opinions will always exist in rhinoplasty, overall consensus exists on striving for natural results, minimizing soft tissue trauma, and structurally supporting the nose for long-term functional and aesthetic outcomes. 4 We would now add that creating a nose with a natural feel is also an important consideration. These goals create guiding principles for surgical planning in revision rhinoplasty.…”
Section: Guiding Principlesmentioning
confidence: 99%
“…Published in 1990, Johnson and Toriumi's "Open Structure Rhinoplasty" emphasized minimizing cartilage resection and employing cartilage grafts to add structural support. 4 Spreader grafting has become essential in reconstructing the roof of the middle vault. 5 Caudal septal extension grafting in conjunction with tongue in groove techniques has been encouraged to secure the medial crura, set projection and rotation, and decrease a hanging columella.…”
Section: Introductionmentioning
confidence: 99%